Post-digestion stabilization of osmium enables quantification by ICP-MS in cell culture and tissue. Issue 13 (6th June 2017) - Klose, Matthias H. M.; Hejl, Michaela; Heffeter, Petra; Jakupec, Michael A.; Meier-Menches, Samuel M.; Berger, Walter; Keppler, Bernhard K.
Abstract : Sample preparation procedures were adapted to reliably quantify an orally active osmium anticancer compound in the organs of treated mice and in cellular accumulation experiments by inductively coupled plasma-mass spectrometry. Abstract : An orally active osmium anticancer compound was reliably quantified in the organs of treated mice by inductively coupled plasma-mass spectrometry (ICP-MS) by adding a stabilizing solution consisting of ascorbic acid, thiourea and EDTA during sample preparation and avoiding oxidizing conditions. The limits of detection (LOD) and quantification (LOQ) of 189 Os were determined in liver tissue to be 0.02 and 0.075 μg kg −1, respectively. In spiked liver tissue, the internal precision showed a relative standard deviation (RSD) of 4%, a matrix recovery of 92% and a digestion recovery of 99%. A similar quantification protocol was developed for cellular accumulation studies in vitro . The cells were lysed with a non-oxidizing lysis buffer consisting of 150 mmol L −1 NaCl, 1.0% Triton X-100, 0.1% SDS, and 50 mmol L −1 Tris at pH 8.0 before adding the stabilizing solution. The osmium compound was compared with an isosteric ruthenium analogue and they displayed similar cellular accumulation and organ distribution profiles.